Needle in a Haystack: Finding Supermassive Black Hole-related Flares in the Zwicky Transient Facility Public Survey - Yael Dgany; Iair Arcavi; Lydia Makrygianni; Craig Pellegrino; D. Andrew Howell (The Astrophysical Journal, 2023)
Transient accretion events onto supermassive black holes (SMBHs), such as tidal disruption events (TDEs), Bowen Fluorescence Flares (BFFs), and active galactic nuclei (AGNs), which are accompanied by sudden increases of activity, offer a new window onto the SMBH population, accretion physics, and stellar dynamics in galaxy centers. However, such transients are rare and finding them in wide-field transient surveys is challenging. Here we present the results of a systematic real-time search for SMBH-related transients in Zwicky Transient Facility (ZTF) public alerts, using various search queries. We examined 345 rising events coincident with a galaxy nucleus, with no history of previous activity, of which 223 were spectroscopically classified. Of those, five (2.2%) were TDEs, one (0.5%) was a BFF, and two (0.9%) were AGN flares. Limiting the search to blue events, the fraction of TDEs nearly doubles to 4.1%, and no TDEs are missed. Limiting the search further to candidate post-starburst galaxies increases the relative number of TDEs to 16.7%, but the absolute numbers in such a search are small. The main contamination source is supernovae (95.1% of classified events), of which the majority (82.2% of supernovae) are of Type Ia. In a comparison set of 39 events with limited photometric history, the AGN contamination increases to ∼30%. Host galaxy offset is not a significant discriminant of TDEs in current ZTF data, but might be useful in higher-resolution data. Our results can be used to quantify the efficiency of various SMBH-related transient search strategies in optical surveys such as ZTF and the Legacy Survey of Space and Time.